2017
DOI: 10.1902/jop.2016.160203
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Literacy and Measures of Periodontal Disease

Abstract: Background Existing evidence demonstrating a relationship between health literacy (HL) and periodontal health is insufficient to identify how providers can help patients manage periodontal disease. This study assesses associations between HL measures (word recognition, numeracy, and conceptual knowledge) and signs of periodontal disease. Methods This study included 325 new patients at a dental school clinic and employed an oral HL (OHL) survey, full-mouth radiographs, and clinical examination. Evaluations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 25 publications
(36 reference statements)
4
37
0
8
Order By: Relevance
“…16 Low OHL is associated with lower levels of dental knowledge and dental information-seeking skills. 8,9 Some prior studies have also shown that low OHL in adults is associated with clinical facets of poor oral health, including fewer teeth and more bleeding sites, 17 as well as a lower frequency of tooth brushing. 18 Associations between OHL and dental care utilization are mixed, however, as 1 study found that low OHL was not associated with recent dental visits, 19 while another found patients with low OHL were more likely to miss their next scheduled dental appointment.…”
Section: Discussionmentioning
confidence: 98%
“…16 Low OHL is associated with lower levels of dental knowledge and dental information-seeking skills. 8,9 Some prior studies have also shown that low OHL in adults is associated with clinical facets of poor oral health, including fewer teeth and more bleeding sites, 17 as well as a lower frequency of tooth brushing. 18 Associations between OHL and dental care utilization are mixed, however, as 1 study found that low OHL was not associated with recent dental visits, 19 while another found patients with low OHL were more likely to miss their next scheduled dental appointment.…”
Section: Discussionmentioning
confidence: 98%
“…Health literacy is a strong predictor of individuals' health, health behaviours and health outcomes. Lack of patient oral health literacy can be a hidden barrier to health care, being associated with lack of preventive behaviours, delayed diagnoses, more invasive treatments, poor adherence to treatment and medical instructions, and consequently poor health outcomes (Baskaradoss, ; Berkman, Davis, & McCormack, ; Berkman, Sheridan, Donahue, Halpern, & Crotty, ; Holtzman, Atchison, Macek, & Markovic, ). Especially in patients with chronic illnesses such as periodontitis, despite the periodontal treatment crucialness, it is essential to find ways to reduce the effects of low health literacy, in order to enhance a proactive and effective involvement of daily self‐care.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is a strong predictor of individuals' health, health behaviours and health outcomes. Lack of patient oral health literacy can be a hidden barrier to health care, being associated with lack of preventive behaviours, delayed diagnoses, more invasive treatments, poor adherence to treatment and medical instructions, and consequently poor health outcomes (Baskaradoss, 2018;Berkman, Davis, & McCormack, 2010;Berkman, Sheridan, Donahue, Halpern, & Crotty, 2011;Holtzman, Atchison, Macek, & Markovic, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Oral health literacy—knowledge on the causes of oral diseases, ability to apply this understanding and to incorporate self‐care behaviours, and also to navigate the healthcare system when needed (Holtzman et al, )—is a research priority (National institute of Dental & Craniofacial Research, National Institute of Health, U.S. Public Health Service, Department of Health Human Services, ), and it is linked to periodontal attachment levels (Wehmeyer, Corwin, Guthmiller, & Lee, ). Sound teaching practices implemented in the dental chair should have an effect on patient oral self‐care practices and treatment compliance (Hughes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of public health interventions on the general public have been undertaken in different countries to tackle this problem with positive results (Gholami, Pakdaman, Montazeri, & Virtanen, 2017;Martensson, Söderfeldt, Halling, & Renvert, 2004) although limited in time. Major issues with these campaigns are the important economic effort required and the limited information gained by the less educated strata of the population (Gholami et al, 2017), who actually need it most (Holtzman, Atchison, Macek, & Markovic, 2017;Volandes & Paasche-Orlow, 2007).…”
mentioning
confidence: 99%